Encryption Techniques and Wireless Power Transfer Schemes - Nur Hazwani Hussin (Institute of Advanced Engineering and Science, 2018)
Wireless power transfer (WPT) is one of the most useful ways to transfer power. Based on power transfer distances, the WPT system can be divided into three categories, namely, near, medium, and far fields. Inductive coupling and capacitive coupling contactless techniques are used in the near-field WPT. Magnetic resonant coupling technique is used in the medium-field WPT. Electromagnetic radiation is used in the far-field WPT. This paper reviews the techniques used in WPT. In addition, energy encryption plays a major role in ensuring that power is transferred to the true receiver. Therefore, this paper reviews the energy encryption techniques in WPT. A comparison between different techniques shows that the distance, efficiency, and number of receivers are the main factors in selecting the suitable energy encryption technique.